Studies on the growth of Otolithes ruber (Bloch & Schneider, 1801), Johnius carutta Bloch, 1793 and Pennahia macrophthalmus (Bleeker, 1850) from Paradeep coast, Orissa, India - Chakraborty, Sushanta Kumar (Indian Journal of Fisheries, 2012)
The growth parameters of three species of sciaenids viz.,, Otolithes ruber, Johnius carutta and Pennahia macrophthalmus from Paradeep coast, Orissa State are reported in the present communication. Employing Bhattacharya-Gulland and Holt plot, the asymptotic length (Lâˆž) and growth co-efficient have been estimated as 511, 305 and 303 mm and 0.67, 0.84 and 0.86 year-1 for O. ruber, J. carutta and P. macrophthalmus respectively. The Ï† prime ranged from 2.90 â€“ 3.24. The growth parameters estimated in the present investigation were compared with the studies conducted for these three species from different parts of the world.